2021
DOI: 10.1097/mol.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of macrophage proliferation and function in atherosclerosis

Abstract: Purpose of reviewMacrophage accumulation within atherosclerotic plaque is a primary driver of disease progression. However, recent advances in both phenotypic and functional heterogeneity of these cells have allowed for improved insight into potential regulation of macrophage function within lesions. In this review, we will discuss recent insights on macrophage heterogeneity, lipid processing, metabolism, and proliferation in atherosclerosis. Furthermore, we will identify outstanding questions in the field tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Low‐density lipoprotein cholesterol (LDL‐C) is a contributor in plaque development and a critical target for intervention for primary and secondary prevention of atherosclerotic cardiovascular disease 17 . In contrast, cholesterol efflux pathways exert anti‐inflammatory and antiatherogenic effects by suppressing proliferative macrophages, 25 inflammation, and inflammasome activation in macrophages 103 . With the development of single‐cell genomic technologies, 104 studies of both murine atherosclerotic models and human atherosclerotic plaques have revealed cell heterogeneity in lesions 105–108 .…”
Section: Comparison Of Macrophage Subsets Between Humans and Micementioning
confidence: 99%
See 2 more Smart Citations
“…Low‐density lipoprotein cholesterol (LDL‐C) is a contributor in plaque development and a critical target for intervention for primary and secondary prevention of atherosclerotic cardiovascular disease 17 . In contrast, cholesterol efflux pathways exert anti‐inflammatory and antiatherogenic effects by suppressing proliferative macrophages, 25 inflammation, and inflammasome activation in macrophages 103 . With the development of single‐cell genomic technologies, 104 studies of both murine atherosclerotic models and human atherosclerotic plaques have revealed cell heterogeneity in lesions 105–108 .…”
Section: Comparison Of Macrophage Subsets Between Humans and Micementioning
confidence: 99%
“…Two opposing phenotypic states have been described in classical macrophage polarization models: the pro‐inflammatory M1 macrophage plays a role induced by bacterial lipopolysaccharide 21,22 and/or interferon‐gamma, and the anti‐inflammatory M2 macrophages that can be activated by interleukin 4 23,24 . Glycolysis and fatty acid oxidation can also play key roles in determining function through differential metabolic activation 25,26 . Macrophages also release oxidized phospholipids, contributing to inflammation, and leading to leukocyte adhesion molecules being expressed on endothelial cells (ECs) 27–30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation